Steering the Course: Negotiating Directions in Alternative Research and Innovation Policies for Transformative Change - Bortz, Gabriela; Gázquez, Ayelén (NOvation — Critical Studies of Innovation, 2025)
This paper explores how inclusive and environmentally focused research and innovation policies challenge dominant models by reshaping directionality and governance for social transformation. It contributes to Critical and Transformative Innovation Studies by addressing key intertwined gaps: the role of agency, the political economy of policy instruments, the politics of continuity, and its territorial grounding. Analytically, it expands a Knowledge Systems approach, promoting a broader, symmetrical view of innovation that values diverse actors, policies, infrastructures, and knowledges. It challenges competitiveness-driven assumptions by exploring how alternative normative directions are negotiated over time. Through two case studies in Argentina—Yogurito (a probiotic yogurt to address malnutrition) and the Paraná River Aquarium (focused on biodiversity conservation)—the paper traces innovation journeys as a process where multiple actors vie to steer its course. Directionality is framed as both a political process of prioritization and decision making amid competing interests and its negotiated outcome, shaped by actors’ visions, knowledge, and policy preferences. The paper also proposes a framework to empirically trace and analyze these evolving pathways. It shows how innovation is steered, which orientations take precedence, and the limits and possibilities of STI as a development driver under enduring structural constraints.